2021
DOI: 10.1371/journal.pgen.1009412
|View full text |Cite
|
Sign up to set email alerts
|

KCTD19 and its associated protein ZFP541 are independently essential for meiosis in male mice

Abstract: Meiosis is a cell division process with complex chromosome events where various molecules must work in tandem. To find meiosis-related genes, we screened evolutionarily conserved and reproductive tract-enriched genes using the CRISPR/Cas9 system and identified potassium channel tetramerization domain containing 19 (Kctd19) as an essential factor for meiosis. In prophase I, Kctd19 deficiency did not affect synapsis or the DNA damage response, and chiasma structures were also observed in metaphase I spermatocyte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…A monoclonal antibody against TRIM41 was produced as previously described [ 16 ]. The DNA encoding mouse TRIM41 (residue 35–85 aa, NP_663352.2) was inserted into pGEX6p-1 (GE healthcare), and the expression vector was transformed into E .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A monoclonal antibody against TRIM41 was produced as previously described [ 16 ]. The DNA encoding mouse TRIM41 (residue 35–85 aa, NP_663352.2) was inserted into pGEX6p-1 (GE healthcare), and the expression vector was transformed into E .…”
Section: Methodsmentioning
confidence: 99%
“…Spread nuclei from spermatocytes were prepared as previously described [ 15 , 16 ]. Seminiferous tubules were unraveled using forceps in ice-cold DMEM (11995065, Thermo Fisher Scientific) and incubated in 1 mg/mL collagenase (C5138, Sigma-Aldrich) in DMEM (20 mL) at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, erasure and re-establishment of proper sex-specific genomic imprinting in these cells must take place simultaneously. Recently, Hirosawa-Takeda et al [ 368 ] and Oura et al [ 369 ] found that the zinc-finger protein (ZFP541) gene is involved in the initiation of meiosis of male germ cells. Whether activation of such genes in somatic cells induces meiosis is of academic interest.…”
Section: Conversion Of Somatic Cells To Germ Cells—artificial Gametesmentioning
confidence: 99%